The Effects of Liquidity, Thin Capitalization, and Audit Quality on Tax Avoidance, with Institutional Ownership as a Moderating Variable (An Empirical Study of Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020–2023) - Adelia Adinda Putri (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to examine the effects of Liquidity, Thin Capitalization, and Audit Quality on Tax Avoidance, with Institutional Ownership serving as a moderating variable. The population consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample was selected using a purposive sampling method, resulting in 22 companies with four years of observation, yielding a total of 88 firm-year observations. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that Liquidity does not have a significant effect on tax avoidance, while Thin Capitalization has a significant effect on tax avoidance. Audit Quality was found to have no significant effect on tax avoidance. Furthermore, Institutional Ownership does not moderate the relationship between Liquidity and tax avoidance, Thin Capitalization and tax avoidance, or Audit Quality and tax avoidance. This study contributes to the existing literature on tax avoidance by providing additional empirical evidence, offers valuable insights for businesses regarding tax avoidance strategies, and provides policymakers with useful considerations for developing more effective tax regulations and policies.